THE DYNAMIC RELATIONSHIP BETWEEN INFLATION AND NON-PERFORMING PROPERTY LOANS IN MALAYSIA - Tham, Kuen Wei; Said, Rosli; Adnan, Yasmin (Journal of Surveying, Construction and Property, 2021)
As costs of services and goods rise in Malaysia while income levels remain low and unemployment rises, there is significant concerns on the rising amount of non-performing property loans that seems to have a close relationship with inflation. Hence, it had been assumed by many where inflation leads to higher non-performing property loans, as a result of rising living costs that cause repayment defaults. In fact, recent findings from various countries across Asia had shown that higher levels of inflation tend to contribute positively to the increase of non-performing property loans. This study is to determine the effects of inflation on non-performing property loans in Malaysia during a unique economic period from 2010 to 2015, where NPLs, which had been declining since 2010 observed its first increase in 2015 after a consistent 5 year decline. This economic occurrence hence, offers a great opportunity of research into the economic observation of 2015 respectively. While there had been studies conducted on non-performing loans, there had been little light shed on the effects of inflation upon non-performing property loans specifically. The method adopted is applying Cointegration test and the Vector Error Correction Model (VECM), as well as Heteroskedasticity Tests, to validate the results in VECM. The results showed that there is a significant co-integration and relationship between non-performing property loans and inflation, lauding long run afflictions upon the real estate market which if not carefully monitored, may result in more property NPL delinquencies in Malaysia.